Bibliometric Analysis Of Character Education Management And Local Wisdom - Alfian Alfian; Aan Komariah; Dedy Achmad Kurniady; Endang Herawan (Jurnal Ilmu Sosial Mamangan, 2024)
This bibliometric study investigates the intersection of character education management and local wisdom, highlighting trends, patterns, and key areas of research from 1997 to 2024. Utilizing comprehensive databases, specifically Scopus, we analyzed 144 scholarly articles, citations, and keywords to map the evolution and impact of these topics in the educational field. The findings reveal a growing interest in integrating local cultural values within character education frameworks, underscoring the significance of contextualized learning in fostering moral and ethical development. Key publications such influential authors, and predominant countries contributing to this discourse, particularly Indonesia, are identified, providing a holistic overview of the current landscape. Co-authorship networks and keyword co-occurrence were visualized using VOSviewer and R Studio Biblioshiny, revealing collaboration patterns and common research themes such as "local wisdom," "character education," and "local knowledge". The potential for future research in the integration of character education and local wisdom is vast, particularly for Indonesian researchers who are already leading in this field. By developing and testing new curricula, focusing on the transition to higher education, fostering international collaborations, and exploring the holistic impact of character education, researchers can contribute significantly to the development of educational practices that nurture well-rounded and culturally aware graduates